Evaluasi Kinerja Dan Tarif Angkutan Umum Perkotaan Di Kabupaten Kuningan (Studi Kasus Trayek Angkot 04 Sadamantra – Pramuka) - Sussendyo, Delviona Jasmine; Hariani, Mira Lestira (Teknik Sipil, Politeknik Negeri Ketapangg, 2024)
Route 04 City Transport is public transportation that operates in Kuningan Regency. This transportation is operated to reduce traffic density and facilitate the people mobility. The aim of the research is to evaluate the performance and tarrifs for Route 04 City Transport whether they meet the requirements or not and to find out what is the passenger’s perception of the performance of the services provided. The methods used in this research are observation, interviews, questionnaires, and collecting primary data on operational performance and tariffs referring to the Director General of Land Transportation’s method SK/687/AJ.206/DRJD/2002 as well as WTP (Willingness To Pay), and service performance referring to the Importance – Performance Analysis (IPA) method. The serults obtained in this research are that there are 3 indicators that do not meet the requirments, namely load factor, service time and fleet availability level. The result of the tariff analysis refer to analysis vehicle operational costs if the tariff with a load factor of 70% is charged at Rp.4.250,44/person and the tariff with load factor of 21,59% is charged at Rp.13.780,9/person and the WTP is mostly desired passengers pay the lowest fare namely IDR 3.000,00. The service performance result obtained using the IPA method contain several attributes that must be maintained, namely in quadrant II and several attributes that must be improved, namely in quadrant I, quadrant III, and quadrant IV